I don’t think I just want points
1. -1
2. -2
3. -12
4. 7
5. -4
Answer:
10
Step-by-step explanation:
20/2=10
10+10=20
17
Answer:
x= -3
Step-by-step explanation:
hello :
-2x+7=-6x-5
-2x+7+6x=-6x-5 +6x
4x+7=-5
4x+7-7=-5-7
4x= -12
x= -12/4
x= -3
3. Look at the picture.
We have the right angle triangle. We know the sum of measures of angles in triangle is equal 180°. Therefore:
![x^o+90^o+43^o=180^o\\\\x^o+133^o=180^o\ \ \ |-133^o\\\\x^o=47^o](https://tex.z-dn.net/?f=x%5Eo%2B90%5Eo%2B43%5Eo%3D180%5Eo%5C%5C%5C%5Cx%5Eo%2B133%5Eo%3D180%5Eo%5C%20%5C%20%5C%20%7C-133%5Eo%5C%5C%5C%5Cx%5Eo%3D47%5Eo)
![Answer:\ \boxed{47^o}](https://tex.z-dn.net/?f=Answer%3A%5C%20%5Cboxed%7B47%5Eo%7D)
4.
Look at the picture.
Use Pythagorean theorem:
![x^2+14^2=(10+x)^2\\\\x^2+196=10^2+2\cdot10\cdot x+x^2\ \ \ \ |-x^2\\\\196=100+20x\ \ \ |-100\\\\20x=96\ \ \ |:20\\\\x=4.8](https://tex.z-dn.net/?f=x%5E2%2B14%5E2%3D%2810%2Bx%29%5E2%5C%5C%5C%5Cx%5E2%2B196%3D10%5E2%2B2%5Ccdot10%5Ccdot%20x%2Bx%5E2%5C%20%5C%20%5C%20%5C%20%7C-x%5E2%5C%5C%5C%5C196%3D100%2B20x%5C%20%5C%20%5C%20%7C-100%5C%5C%5C%5C20x%3D96%5C%20%5C%20%5C%20%7C%3A20%5C%5C%5C%5Cx%3D4.8)
![Used:\ (a+b)^2=a^2+2ab+b^2](https://tex.z-dn.net/?f=Used%3A%5C%20%28a%2Bb%29%5E2%3Da%5E2%2B2ab%2Bb%5E2)
![Answer:\ \boxed{4.8\ units}](https://tex.z-dn.net/?f=Answer%3A%5C%20%5Cboxed%7B4.8%5C%20units%7D)
5.
TRUE: 1; 2; 4
6.
We find a slope of the line OP:
![m=\dfrac{y_2-y_1}{x_2-x_1}\\\\O(2;\ 6)\to x_1=2;\ y_1=6\\\\P(4;\ 3)\to x_2=4;\ y_2=3\\\\m=\dfrac{3-6}{4-2}=\dfrac{-3}{2}](https://tex.z-dn.net/?f=m%3D%5Cdfrac%7By_2-y_1%7D%7Bx_2-x_1%7D%5C%5C%5C%5CO%282%3B%5C%206%29%5Cto%20x_1%3D2%3B%5C%20y_1%3D6%5C%5C%5C%5CP%284%3B%5C%203%29%5Cto%20x_2%3D4%3B%5C%20y_2%3D3%5C%5C%5C%5Cm%3D%5Cdfrac%7B3-6%7D%7B4-2%7D%3D%5Cdfrac%7B-3%7D%7B2%7D)
We have:
![OP:\ y=-\dfrac{3}{2}x+b](https://tex.z-dn.net/?f=OP%3A%5C%20y%3D-%5Cdfrac%7B3%7D%7B2%7Dx%2Bb)
Now, we must find the slope of the line perpendicular to the line OP.
We know:
![k:y=m_1x+b;\ l:y=m_2x+c\\\\k\ \perp\ l\iff m_1m_2=-1](https://tex.z-dn.net/?f=k%3Ay%3Dm_1x%2Bb%3B%5C%20l%3Ay%3Dm_2x%2Bc%5C%5C%5C%5Ck%5C%20%5Cperp%5C%20l%5Ciff%20m_1m_2%3D-1)
therefore
![-\dfrac{3}{2}m_2=-1\ \ \ |\cdot\left(-\dfrac{2}{3}\right)\\\\m_2=\dfrac{2}{3}](https://tex.z-dn.net/?f=-%5Cdfrac%7B3%7D%7B2%7Dm_2%3D-1%5C%20%5C%20%5C%20%7C%5Ccdot%5Cleft%28-%5Cdfrac%7B2%7D%7B3%7D%5Cright%29%5C%5C%5C%5Cm_2%3D%5Cdfrac%7B2%7D%7B3%7D)
So. We have the answer! :)